RISK ANALYSIS OF BLACK TEA PRODUCTION AT PTPN IV BAH BUTONG SIMALUNGUN REGENCY - Yohana Christy; Wiludjeng Roessali; Suryani Nurfadillah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Tea production in Indonesia is experiencing fluctuations. These conditions cause losses, so the company needs to handle the risks that occur. This study aims to analyze the risk level of black tea production, the incidence and risk agents as well as the risk management strategy of black tea production. This research was conducted in September-October 2021 at PTPN IV Bah Butong, Simalungun Regency. Location determination is carried out purposively with consideration as a producer of tea production. The research method used is a case study. The sampling method uses judgement sampling. Observation and interview data collection techniques. Data analysis using the Coefficient of Variation (CV) and the House of Risk (HoR) method. The results showed that the risk at PTPN IV Bah Butong was relatively high with a CV of 22.46% and fluctuating. The identification results found 8 risk events, namely fluctuation of tea production, quantity and quality tea leaves is low, tea leaves are scattered, low quantity and quality dry tea, delays in the production process, there are weeds and twigs, as well as 16 sources of risk, namely extreme weather, leaves attacked by pests, attacks of smallpox and helopeltis, pest management diseases are less than optimal, less attention to the picking cycle, limited fertilizer and application delays, non-uniform harvesting, less clean leaf sorting, insufficient withering, human error, scattered dry tea, malfunctions of the hauling machine, picking and transportation. The identification results found 8 handling strategies to minimize losses due to emerging risks.